Marx on ecology and gender in the era of global climate change - Jover, Elmer L. (Iloilo City UP Visayas, 2009)
"This paper discusses ecological ideas culled from Karl Marx's writings, particularly his views on soil depletion. Marx laid down some foundations for ecological sustainability as he addressed this foremost critiqued as a direct consequence of capitalistic agriculture, the paper likewise looks into Marx's failure to address gender concerns in his writings, especially since environmental issues have differential effects for men and women. Such oversight on Marx's part serves as parallelism to the current climate change discourses, where gender issues are largely not yet considered as crucial factors."
Keywords: Soil conservation; Climate change